Stranger things. The voyage - Moreci, Michael (Dark Horse Books, 2024)
"Captain Jacoby is too broke to reject a shady deal from a group of Russians looking to get from Alaska back to Kamchatka on his freighter ship, The Persophone, but things get turned upside down when a crew member gets butchered. The captain and his crew suspect something far stranger at play"--